تکملہ فتح الملہم کے اہم مصادر ومراجع اور ان سے استفادہ کے مناہج: Major Sources and References of Takmilah Fath al-Mulhim and the Scholarly Approaches to Their Utilization (Al-Qamar, 2025)
The field of Hadith studies is one of the most intricate and specialized disciplines within Islamic scholarship, with its subfields expanding into hundreds of distinct areas. Islamic scholars have authored thousands of monographs dedicated to the interpretation and elucidation of Hadith, resulting in numerous voluminous works, each contributing significantly to the understanding and explanation of Prophetic traditions. Among these, one of the most notable contributions is "Takmilah Fath al-Mulhim,"a scholarly endeavor by Mufti Muhammad Taqi Usmani, reflecting years of rigorous academic effort. This work serves as a continuation of the commentary on Sahih Muslim initiated by Mufti Shabbir Ahmad Usmani, who was able to complete it only up to the "Book of Marriage" due to his political obligations and subsequent demise. Mufti Muhammad Taqi Usmani, completing the unfinished work, brought the project to its conclusion over a span of eighteen years and nine month. This article provides an analysis of the primary sources and a reference utilized in “Takmilah Fath al-Mulhim” and explores the scholarly methods for their effective utilization.
Keywords: Hadith studies, Takmilah Fath al-Mulhim, primary sources & scholarly methods